Differences between elite, junior and non-rowers in kinematic and kinetic parameters during ergometer rowing - Cerne, T.; Kamnik, R.; Vesnicer, B.; Zganec Gros, J.; Munih, M. (Human Movement Science, 2013)
This paper presents an analysis of the rowing parameters of differently skilled rowers. The study focuses on technique dependency on stroke rate. Five elite, five junior and five non-rowers participated, and the biomechanics of rowing on an ergometer was analyzed at stroke rates of 20, 26 and 34 str/min. The results show that elite rowers use a similar, consistent rowing technique at all stroke rates, the technique of junior rowers follows similar principles, while the technique of non-rowers varies. Elite rowers` stroke length, handle motion and body posture do not change with stroke rate while the ratio of stroke phases, maximum forces, stroke work and joint loadings are constant at the same stroke rate but dependent on stroke rate. Junior rowers with stroke rate change also the stroke length. In non-rowers the differences can be observed in the handle motion and body posture during the stroke, their stroke length changes with stroke rate while the ratio of stroke phases stays constant. Although different movement execution is evident and variable with stroke rate, non-rowers demonstrate a consistent pattern at the same stroke rate. On the basis of the results, the crucial parameters that differentiate elite, junior, and non-rowers are identified.